Brazilian highways: Importance of devices for the passage of fauna (Research, Society and Development, 2022)
This work will address the creation of highways that remain in environmental effects, in order to insert them into their use and the dispositions of the faunas that are inserted, since the fragments that they exert as a result of quality changes are verified. Therefore, the aspects and means of this structuring were decisive, a form that changes over the changes and classifies as contemplations of consequences. Requirement guarantees make accessing the passages and functioning in biodiversity easier. In order to emphasize the procedures and resources that are used in their presentations, thus distributing stretches of ecological roads throughout Brazil. The supplies provided on the fauna of small accident hazard in road methods, which are generated in the main types of deaths of the stretches. However, the improvement control is elaborated, causing the installations to be implemented that reduce the probabilities generated.